The Influence of Graphene Oxide on the Performance of Concrete: A Quantitative Analysis of Mechanical and Microstructural Properties - Christhian Benavente; Anjhinson Romero; Jorge Napa; Alexis Sanabria; Yanett Landivar; Leo La Borda; Pablo Pezo; Abel Muñiz; Marco Muñiz (Buildings)
The incorporation of graphene oxide (GO) into cementitious materials has gained significant attention due to its potential to enhance both the mechanical and microstructural properties of concrete. This study investigates the effect of GO on the compressive strength, flexural strength, indirect tensile strength, and elastic modulus of concrete with a design strength of 280 kg/cm2. Additionally, scanning electron microscopy (SEM) analysis, energy-dispersive X-ray spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR), thermogravimetric analysis (TGA), and X-ray diffraction (XRD) were conducted to assess microstructural modifications induced by GO. The results indicate that an optimal GO dosage of 0.05% leads to notable improvements, with increases of 14.61% in compressive strength, 12.33% in indirect tensile strength, 6.09% in flexural strength, and 27.38% in elastic modulus. Microstructural analysis revealed a 16.28% reduction in pore and crack size, which directly contributes to improved structural integrity by enhancing matrix densification and reducing potential crack propagation. Furthermore, a 44.49% increase in the Ca/Si ratio was observed, suggesting improved cement hydration and bond formation. The increase in silicon-based compounds and a reduction in portlandite content indicate improved hydration kinetics. These findings provide valuable insights into the reinforcing mechanisms of GO in cementitious materials and lay the groundwork for future applications in high-performance concrete for sustainable construction.